A sono-responsive antibacterial nanosystem co-loaded with metformin and bone morphogenetic protein-2 for mitigation of inflammation and bone loss in experimental peri-implantitis - Hu, Bo; Qiao, Wang; Cao, Yang; Fu, Xiaoming; Song, Jinlin (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Dental implants have become an increasingly popular option for replacing missing teeth, and the prevalence of peri-implantitis has also increased, which is expected to become a public health problem worldwide and cause high economic and health burdens. This scenario highlights the need for new therapeutic options to treat peri-implantitis. Methods: In this study, we proposed a novel sono-responsive antibacterial nanosystem combined with metformin (Met) and bone morphogenetic protein-2 (BMP-2) to promote efficacy in treating peri-implantitis. We introduced the zeolitic imidazolate framework-8 (ZIF-8) as a carrier for hematoporphyrin monomethyl ether (HMME) to enhance the antibacterial effect of sonodynamic antibacterial therapy and tested its reactive oxygen species (ROS) production efficiency and bactericidal effect in vitro. Afterward, HMME-loaded ZIF-8, BMP-2-loaded polylactic acid-glycolic acid (PLGA), and Met were incorporated into gelatin methacryloyl (GelMA) hydrogels to form HMME@ZIF-8/Met/BMP-2@PLGA/GelMA composite hydrogels, and the biocompatibility of which was determined in vitro and in vivo. A bacterial-induced peri-implantitis model in the maxilla of rats was established to detect the effects of the composite hydrogels with adjunctive use of ultrasound on regulating inflammation and promoting bone tissue repair in vivo. Results: The results indicated that HMME@ZIF-8 with ultrasound stimulation demonstrated more better ROS production efficiency and antimicrobial efficacy. The composite hydrogels had good biocompatibility. Ultrasound-assisted application of the composite hydrogels reduced the release of the inflammatory factors IL-6 and TNF-α and reduced bone loss around the implant in rats with bacterial-induced peri-implantitis. Conclusion: Our observations suggest that HMME@ZIF-8 may be a new good sonosensitizer material for sonodynamic antibacterial therapy. The use of HMME@ZIF-8/Met/BMP-2@PLGA/GelMA composite hydrogels in combination with ultrasound can provide a novel option for treating peri-implantitis in the future.